A Suzaku X-ray observation of one orbit of the supergiant fast X-ray transient IGR J16479-4514 - Sidoli, Lara; Esposito, Paolo; Sguera, Vito; Bodaghee, A.; Tomsick, J. A.; Pottschmidt, K.; Rodriguez, Jerome; Romano, Patrizia; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2013)
We report on a 250 ks long X-ray observation of the supergiant fast X-ray transient IGR J16479-4514 performed with Suzaku in 2012 February. During this observation, about 80 per cent of the short orbital period (P-orb similar to 3.32 d) was covered as continuously as possible for the first time. The source light curve displays variability of more than two orders of magnitude, starting with a very low emission state (10(-13) erg cm(-2) s(-1); 1-10 keV) lasting the first 46 ks, consistent with being due to the X-ray eclipse by the supergiant companion. The transition to the uneclipsed X-ray emission is energy dependent. Outside the eclipse, the source spends most of the time at a level of 6-7 x 10(-12) erg cm(-2) s(-1) punctuated by two structured faint flares with a duration of about 10 and 15 ks, respectively, reaching a peak flux of 3-4 x 10(-11) erg cm(-2) s(-1), separated by about 0.2 in orbital phase. Remarkably, the first faint flare occurs at a similar orbital phase of the bright flares previously observed in the system. This indicates the presence of a phase-locked large-scale structure in the supergiant wind, driving a higher accretion rate on to the compact object. The average X-ray spectrum is hard and highly absorbed, with a column density, N-H, of 1023 cm-2, clearly in excess of the interstellar absorption. There is no evidence for variability of the absorbing column density, except that during the eclipse, where a less absorbed X-ray spectrum is observed. A narrow Fe K alpha emission line at 6.4 keV is viewed along the whole orbit, with an intensity which correlates with the continuum emission above 7 keV. The scattered component visible during the X-ray eclipse allowed us to directly probe the wind density at the orbital separation, resulting in rho(w) = 7 x 10(-14) g cm(-3). Assuming a spherical geometry for the supergiant wind, the derived wind density translates into a ratio. M-w/v(infinity) = 7 x 10(-17) M-circle dot km(-1) which, assuming terminal velocities in a large range 500-3000 km s(-1), implies an accretion luminosity two orders of magnitude higher than that observed. As a consequence, a mechanism should be at work reducing the mass accretion rate. Different possibilities are discussed.
Keywords: accretion; accretion discs; X-rays: binaries; supergiants; X-rays: individual: IGR J16479-4514